ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI DIVIDEND PAYOUT RATIO (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di BEI 2015-2017) - Lie, Maria Jeannifer; OSESOGA, MARIA STEFANI (Universitas Multimedia Nusantara, 2020)
Abstract- The objective of the research is to obtain empirical evidence of the effect of Return on Assets, Current Ratio, Debt to Equity Ratio, and Managerial Ownership towards Dividend Payout Ratio. Companies need to know any factors to determine the optimal dividend policy. The sample in this research is selected by using purposive sampling method and the secondary data used in this research was analyzed by using multiple regression method. The total amount of sample in this research is 13 firms which is registered as manufacturing sector in BEI for the year 2015-2017; published financial reports using Rupiah currency; audited by independent auditor; published financial reports for January 1 until December 31 periods, have positive net income, declared cash dividend, did not do stock split/ reverse stock split; and have managerial ownership on shareholders structure. The result of this research are Return on Assets, Current Ratio, Debt to Equity Ratio, and Managerial Ownership simultaneously has significant effect towards Dividend Payout Ratio. Partially, variable Return on Assets, and Managerial Ownership have positive significant effect on Dividend Payout Ratio. While Current Ratio and Debt to Equity Ratio does not have significant effect towards Dividend Payout Ratio.